Emerging Trends in Wireless Electric Vehicle Charging Systems: Advancements and Challenges - Aymen Alkurbo; Radwan Elbasir; Tarek Eseholi; Osama Abuzaid; Yousef Abueejela (African Journal of Advanced Pure and Applied Sciences, 2023)
Today, the adoption of electrified transportation presents a significant opportunity to mitigate greenhouse gas emissions and address the challenges posed by rising fuel costs. To facilitate the widespread adoption of electric vehicles (EVs), it is crucial to establish diverse and user-friendly charging networks that are environmentally sustainable. Wireless electric vehicle charging systems (WEVCS) have emerged as a promising alternative technology, offering the potential to address the limitations associated with plug-in charging methods. This paper provides an overview of the existing wireless power transfer technologies available for EVs, highlighting their potential to revolutionize the charging infrastructure and enhance the convenience and accessibility of EV charging. Moreover, the communication network within the IoE relies on an internet-like information flow, enabling bidirectional data exchange between devices. Reliability and connectivity enhancement are key considerations for the communication systems employed. Overall, the integration of EVs and the IoE framework holds immense potential for revolutionizing the power system, optimizing energy utilization, and promoting sustainable energy practices.